Camouflaged angiogenic BMP-2 functions exposed by pico-paracrine biohybrids - Jennissen, Herbert P. (Frontiers in Bioengineering and Biotechnology, 2023)
Although commercial human bone morphogenetic protein 2 (BMP-2) creates a huge revenue of nearly half a billion USD per year, there are still many unknowns in respect to its possible intrinsic functions and especially in respect to its mechanisms of action in the human body. One such unknown function, recently detected with biohybrids, is its direct influence on blood vessel formation and inhibition, which will be reviewed, expanded and discussed in this paper. This paper is part of the Research Topic: Insights in Biomaterials 2022/2023 –Novel Developments, Current Challenges, and Future Perspectives.